PENGARUH IKLIM SEKOLAH DAN KETELADANAN GURU TERHADAP PERILAKU DISIPLIN SISWA SEKOLAH DASAR - Denia Putri Rizkia; Herpinah Imel Eka Mulyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the influence of school climate and teacher role modeling on elementary school students’ disciplinary behavior. The background of this research is the persistence of disciplinary issues among students, which are assumed to be closely related to the quality of the school environment and the example set by teachers. The objective of this study is to analyze both the partial and simultaneous effects of school climate and teacher role modeling on student’discipline. This research employed a quantitative approach using a correlational design. The population consisted of elementary school students, with samples selected through proportional random sampling. Data were collected using validated questionnaires and analyzed using multiple linear regression techniques. The results indicate that school climate has a positive and significant effect on students’ disciplinary behavior (β = 0.312; p < 0.05). Teacher role modeling also shows a significant positive influence on student discipline (β = 0.458; p < 0.05). Simultaneously, school climate and teacher role modeling significantly contribute to students’ disciplinary behavior (F = 28.94; p < 0.05), with teacher role modeling showing a stronger influence. These findings suggest that creating a supportive school climate and enhancing teachers’ exemplary behavior are essential strategies for fostering discipline in elementary school students.